The influence of varied parenteral nutrition protocols on the surgical incidence and prognosis of retinopathy of prematurity in preterm neonates - Sun, Yafei; Wang, Teng; Lin, Ruixia; Xu, Xuejun (Frontiers in Pediatrics, 2025)
ObjectiveThis retrospective cohort study aimed to assess the impact of different parenteral nutrition (PN) protocols on the incidence and prognosis of retinopathy of prematurity (ROP) in preterm infants.MethodsMedical records of 87 preterm infants admitted to the neonatal intensive care unit between October 2019 and October 2022 were retrospectively analyzed. The infants were non-randomly allocated into two groups based on the PN protocols they received: the fish oil group (41 cases) received PN with high n-3 fatty acid-containing lipid emulsions, while the non-fish oil group (46 cases) received PN with medium and long-chain lipid emulsions. Fatty acid profiles were assessed on the first day of hospitalization and after 14 days of PN. The incidence of ROP at 4 and 6 weeks after birth was compared, along with the time taken to regain birth weight, achieve full enteral feeding, duration of mechanical ventilation, and ROP surgical rate during hospitalization.ResultsOn the first day of hospitalization, there were no significant differences in DHA, EPA, and AA levels between the two groups. However, after 14 days of PN, the fish oil group showed significantly higher DHA levels and lower AA levels compared to the non-fish oil group. The fish oil group required less time to achieve full enteral feeding compared to the non-fish oil group. There were no significant differences in other blood parameters between the two groups. The levels of liver enzymes (ALT, TBA, AST, γ-GT) were significantly lower in the fish oil group. There were no significant differences in the overall incidence of ROP and mild ROP between the two groups at 4 and 6 weeks after admission. However, the fish oil group had a significantly higher incidence of severe ROP and a significantly lower surgical rate compared to the non-fish oil group.ConclusionEarly administration of lipid emulsions enriched with n-3 fatty acids in preterm infants has a preventive effect on severe ROP. This intervention is associated with higher serum DHA levels and lower AA levels, shorter time to achieve full enteral feeding, and reduced surgical rate for ROP. Further research is needed to optimize PN strategies in preterm infants with ROP.